Internet and Social Media in European Minority Languages: Analysis of the Digitalization Process - Ferré-Pavia, Carme; Zabaleta, Iñaki; Gutierrez, Arantza; Fernandez-Astobiza, Itxaso; Xamardo, Nicolás (USC Annenberg School for Communication & Journalism, 2018)
The aim of this article is to analyze the Internet reality and performance of European minority language media, including a comparison of the evolution of traditional media websites between 2009 and 2016. The 10 language communities are Catalan, Galician, Basque, Welsh, Irish, Frisian, Breton, Corsican, Scottish Gaelic, and Sámi. The quantitative and qualitative inquiry is based on the data of the complete censuses of the 10 media systems. To evaluate Internet and social media activity, as well as areas of improvement, we gathered information from an adequate sample of media editors and managers. The findings indicate that nine out of 10 news organizations have some presence on the Internet in the form of websites and/or social media. Compared with data collected in 2009, the average number of media organizations with no Internet presence has decreased from 29% to 9.2%. A niche of traditional media, however, remains outside the digital and online world.